Humic acids derived from Leonardite to improve enzymatic activities and bioavailability of nutrients in a calcareous soil - Sun, Qian; Liu, Jianlong; Huo, Lianfei; Li, Yuncong C; Li, Xue; Xia, Liru; Zhou, Zhongkai; Zhang, Meina; Li, Bin (International Journal of Agricultural and Biological Engineering, 2020)
Understanding the role of humic substances in soils is important for developing and utilizing organic fertilizers or soil amendments for sustainable agriculture. The objective of this study was to determine the effects of different fractions of humic acids derived from Leonardite on enzymatic activities and bioavailability of nutrients in a soil. The experiment was carried out by mixing different factions of humic acids with a soil and incubated for 70 d. The treatments included five factions of humic acids (HS1 (low molecular weight), HS2 (medium molecular weight), HS3 (large molecular weight, SED (sediment of fractions), HS (mixture of HS1, HS2, and HS3)), raw Leonardite (IM) and a control (no addition of humic acid). Experimental results showed that application of humic acids significantly improved acid and alkaline phosphatase activities, especially with HS1. Humic substances with high molecular weights significantly inhibit urease activity, and the optimal application rate was 600 kg/hm2 of humic substances with the high molecular weights. Concentrations of NH4+-N were decreased with increasing humus applications. All treatments (HSmix, HS1, HS2, HS3, IM, SED) did not affect the soil contents of Ca, although soil concentrations of K, P, Cu, Zn were increase significantly when small molecular weight humus (HS1) was applied. Keywords: humic acid, molecular weight, Leonardite, enzyme, nutrient content DOI: 10.25165/j.ijabe.20201303. Citation: Sun Q, Liu J L, Huo L F, Li Y C, Li X, Xia L R, et al. Humic acids derived from Leonardite to improve enzymatic activities and bioavailability of nutrients in a calcareous soil. Int J Agric & Biol Eng, 2020; 13(3): 200–205.